What are People's Experiences of a Novel Cognitive Behavioural Therapy for Bipolar Disorders? A Qualitative Investigation with Participants on the TEAMS Trial. (21st September 2016) - Joyce, Emmeline; Tai, Sara; Gebbia, Piersanti; Mansell, Warren
Abstract : Background: Psychological interventions for bipolar disorders typically produce mixed outcomes and modest effects. The need for a more effective intervention prompted the development of a new cognitive behavioural therapy, based on an integrative cognitive model ('Think Effectively About Mood Swings' [TEAMS] therapy). Unlike previous interventions, TEAMS addresses current symptoms and comorbidities, and helps clients achieve long‐term goals. A pilot randomized controlled trial (the TEAMS trial) of the therapy has recently concluded. This study explored participants' experiences of TEAMS, recommendations for improvement and experiences of useful changes post‐therapy. Methods: Fourteen TEAMS therapy participants took part in semi‐structured interviews. Their accounts were analysed using interpretative thematic analysis. Two researchers coded the dataset independently. Member checks were conducted of the preliminary themes. Results: Two overarching themes; 'useful elements of therapy' and 'changes from therapy' encompassed 12 emerging subthemes. Participants appreciated having opportunities to talk and described the therapy as person‐centred and delivered by caring, approachable and skilled therapists. Some recommended more sessions than the 16 provided. Helpful therapeutic techniques were reported to be, normalization about moods, methods to increase understanding of moods, relapse‐prevention, reappraisal techniques and metaphors. However, some did not find therapeutic techniques helpful. Post‐therapy, many reported changes in managing mood swings more effectively and in their thinking (although some participants reported changes in neither). Many described increased acceptance of themselves and of having bipolar disorder, increased productivity and reduced anxiety in social situations. Conclusions: The present study evaluates participants' therapy experiences in detail, including aspects of therapy viewed as helpful, and meaningful post‐therapy outcomes. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioner Message: This is the first paper to qualitatively explore people's experiences of individual psychotherapy for bipolar disorders. It highlights elements of psychotherapy described as particularly helpful or unhelpful and the clinical changes viewed as most impactful. Participants reported benefitting in a number of ways from TEAMS therapy. They valued learning to reappraise and problem‐solve situations and manage moods. Participants identified TEAMS techniques as helpful, such as exploring advantages and disadvantages of moods, and building healthy self‐states.